Transcriptome analysis revealed the role of moderate exogenous methyl jasmonate treatments in enhancing the metabolic pathway of L-borneol in the Blumea balsamifera - Guan, Lingliang; Lin, Na; Wan, Lingyun; Yu, Fulai; Chen, Xiaolu; Xie, Xiaoli; Yuan, Chao; Soaud, Salma A.; Abd Elhamid, Mohamed A.; Heakel, Rania M. Y.; Wang, Linghui; El-Sappah, Ahmed H. (Frontiers in Plant Science, 2024)
Introduction Blumea balsamifera L. (Ainaxiang) DC. is a perennial herb of the compositae family. It is also the primary source of natural borneol. Endo-borneol, the principal medical active element in B. balsamifera, is anti-inflammatory, antioxidant, and analgesic; enhances medicine absorption; refreshes; and is used as a spice and in cosmetic. Industrialization of B. balsamifera is limited by its low L-borneol concentration. Thus, understanding the accumulation pattern of the secondary metabolite endo-borneol and its synthesis process in secondary metabolism is critical for increasing B. balsamifera active ingredient content and cultivation efficiency. Methods In this work, B. balsamifera was treated with varying concentrations (1.00 and 10.00 mmol/L) of methyl jasmonate (MeJA) as an exogenous foliar activator. The physiological parameters and L-borneol concentration were then assessed. Transcriptome sequencing of B. balsamifera-induced leaves was used to identify key genes for monoterpene synthesis. Results The treatment effect of 1 mmol/L MeJA was the best, and the leaves of all three leaf positions accumulated the highest L-borneol after 120 h, correspondingly 3.043 mg·g−1 FW, 3.346 mg·g−1 FW, and 2.044 mg·g−1 FW, with significant differences from the control. The main assembly produced 509,285 transcripts with min and max lengths of 201 and 23,172, respectively. DEG analysis employing volcano blots revealed 593, 224, 612, 2,405, 1,353, and 921 upregulated genes and 4, 123, 573, 1,745, 766, and 763 downregulated genes in the treatments D1_1vsCK, D1_10vsCK, D2_1vsCK, D2_10vsCK, D5_1vsCK, and D5_10vsCK. Interestingly, when exposed to MeJA treatments, the MEP pathway’s unigenes express themselves more than those of the MVA route. Finally, when treated with 1 mmol/L, the genes DXR, DXS, and GPS showed increased expression over time. At the same time, a 10 mmol/L therapy resulted in elevated levels of ispH and GGPS. Discussion Our preliminary research indicates that exogenous phytohormones can raise the level of L borneol in B. balsamifera (L.) DC when given in the appropriate amounts. The most significant discovery made while analyzing the effects of different hormones and concentrations on B. balsamifera (L.) DC was the effect of 1 mmol/L MeJA treatment.